Development of a performance-based high pressure feed water heater model for Flownex SE - Thakaso, Matete (Department of Mechanical Engineering, 2015)
Feed-water heaters (FWHs) are an integral part of the power plant with respect to the overall heat recovery, and thus its efficiency. While the main purpose of the FWHs is to heat up the feed-water before being sent to the boiler, there are more added advantages owing to the installation of this equipment to the power plant such as less heat being removed to the atmosphere at the condenser. This report aims at understanding the different types of FWHs in operation and understanding how heat is transferred from the bled steam into the feed-water, and using the understanding to model a transient FWH. The FWH model is a building block towards building a complete transient power plant model. Process operations are all subject to constraints of some sort. The limitations can be in the form of physical geometry, process parameters or lack of correlations that relate known data. The constraints vary in their complexity, and depending on the type of constraints a different mathematical modelling technique can be applied to implement the FWH model. The grey-box modelling technique was chosen to be the appropriate one for analysis as it captures the dynamics that depend on the first principles and correlations whilst still using the global inlet and outlet properties of the FWH. The FWHs have three zones; de-superheating, condensing and sub-cooling zones. The heat transfer characteristics of the three zones are different, and thus their heat duties with the condensing taking a significant amount of the heat duty.